(untitled) (Research, Society and Development, 2021)
Introduction: COVID-19, also known as coronavirus, is the virus that has afflicted the entire world population. Therefore, it is necessary to know the impacts caused by dietary changes that have affected nutrition and food security in this pandemic scenario. In this way, a bibliographic survey was carried out with literature researched on Google Scholar, with ten articles selected within the proposed theme. It demonstrated that the restrictions caused by social isolation affected individuals psychologically and mentally, directly affecting eating habits, as there was an increase in the consumption of ultra-processed foods, a decrease in the consumption of fresh foods, a reduction in physical activities, weight gain. These aspects cause malnutrition, consequently malnutrition and obesity. Thus, the immune system is reaching, generating aggravating outcomes in patients with COVID-19. In view of the above, it is necessary to have a follow-up from the nutritionist, to obtain guidance on good eating behavior combined with the practice of physical exercises that can help metabolism to obtain positive reactions to the treatment of this pathology.